CLIMATE CHANGE AND CARDIOVASCULAR HEALTH: A SYSTEMATIC REVIEW - Szlegiel, Igor; Gwiaździńska, Oktawia; Strzykała, Anita; Lewandowski, Jakub; Myszak, Denis; Hovsepyan, Izabela (International Journal of Innovative Technologies in Social Science, 2026)
Background: Climate change is increasingly recognized as a major cardiovascular threat because it intensifies exposure to heat, cold, air pollution, wildfire smoke, and extreme weather events. These stressors can trigger acute cardiovascular events, increase mortality, and disrupt emergency care, particularly among older adults and patients with pre-existing cardiovascular disease.Methods: This narrative review synthesizes verified evidence from recent systematic reviews, major cardiology reviews, European reports, and Polish studies relevant to climate-sensitive cardiovascular disease. The emphasis is on acute events, mortality, vulnerable populations, and emergency care implications, with particular attention to Europe and Central Europe.Results: The strongest evidence links extreme temperature with increased cardiovascular morbidity and mortality, while air pollution and wildfire smoke appear to worsen vascular inflammation, thrombosis, and arrhythmic risk. Climate-related weather disruptions may also limit timely access to emergency and inpatient cardiovascular care. Polish data show substantial heat-related mortality during hot summers and support the relevance of climate-sensitive cardiovascular risk in Central Europe.Conclusions: Climate change is already influencing cardiovascular emergencies and mortality in current practice, not only in long-term projections. Climate adaptation, environmental prevention, and emergency preparedness should therefore be incorporated into cardiovascular care, especially in Poland and neighboring Central European settings.